0501 Use of the AASM Recommended Hypopnea Definition to Assess the Association Between Obstructive Sleep Apnea and 2018 ACC/AHA Blood Pressure Thresholds. (12th April 2019) - Quan, Stuart F; Sogol, Javaheri; Budhiraja, Rohit; Parthasarathy, Sairam
Abstract: Introduction: The association between obstructive sleep apnea (OSA) and hypertension in prior studies has been determined using a definition of hypopnea requiring a 4% O2 desaturation. However, the AASM recommends using a 3% O2 desaturation or an arousal. This analysis assesses the relationship between OSA and hypertension utilizing the AASM recommended definition and the 2018 ACC/AHA blood pressure (BP) guidelines. Methods: Data from 6113 participants from the baseline examination of the Sleep Heart Health Study were analyzed. The apnea hypopnea index (AHI) using home polysomnography and defined by a 3% O2 desaturation or an arousal was classified into 4 categories of OSA severity: <5, 5-<15, 15-<30 and ≥30/hour. Three definitions of dichotomous BP elevation were used: Elevated (>120/80 or use of hypertension medications [meds]), Stage 1 or Stage 2 (>130/80 or meds), Stage 2 (>140/90 or meds). The association between elevated BP and/or hypertension and OSA severity was assessed using logistic regression controlling for demographics and body mass index (BMI). Additional analyses utilized multiple linear regression to determine the relationship between natural log AHI, and systolic and diastolic BP controlling for the same covariates. Results: For all definitions of BP elevation, increasing OSA severity was associated with greater likelihood of an elevated or hypertensive status in fully adjusted models: Elevated OR (95%CI): 1.30 (1.10-1.54), 1.41 (1.15-1.72) 1.69 (1.32-2.17); Stage 1: 1.27 (1.09-1.49), 1.36 (1.13-1.63), 1.58 (1.27-1.97); Stage 2: 1.07 (0.92-1.26), 1.22 (1.02-1.45), 1.38 (1.12-1.69) for AHI 5-<15, 15-<30 and >30 /hour (<5 /hour=reference). Linear regression found that AHI was associated with both systolic and diastolic blood pressure in fully adjusted models. Conclusion: Use of the AASM recommended definition of hypopnea as a component of the AHI is associated with the presence of an elevated or hypertensive BP. This suggests that use of a 4% O2 desaturation requirement to identify patients with OSA is too stringent. Additional analyses will be required to assess whether using a 3% O2 or arousal criterion is predictive of incident hypertension. Support (If Any): NHLBI